Evangelicals and the Evangel - Michael Horton (STTRII, 2021)
In this article, the author argues on the importance of the Reformation. Despite over 500 years has passed since the reformation, the roman catholic church has not moved towards the true understanding of the gospel, in terms of justification as being declared right. Furthermore, in the author's context of American Evangelism, pelagianism seems taking over the mindset of the biblically illiterate. The preaching of the evangel that justifies the ungodly must be the call of the day.